Smuggling Plants: Memory and Accountability in the Experience of a Latest-Generation Italian Canadian - Buiani, Roberta (Italian Canadiana, 2024)
In this paper, I reflect on my experience of making home and homeliness as a recent Canadian and on the significance that bringing a seed or a plant into an adoptive country may have for others. I ask how this gesture may be interpreted through a pluralistic, non-anthropocentric view: how can I, a relatively recent settler, acknowledge and address the consequences and the contradictions generated from the practice of seed and plant smuggling described above? How can I become more accountable for my presence in my new adoptive home, and at the same time find ways to maintain and strengthen my identity as a symbiotic being (and not as an island) in dialogue with the land, the populations, and the cultures that host me?